The Influence Of Perceived Ease Of Use And Perceived Usefulness On The Intention To Use Qris Among Students In Pontianak City With Trust As An Intervening Variable - Priyanda, Tazkia; Fachri, Helman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of Perceived Ease of Use (PEU) and Perceived Usefulness (PU) on Intention to Use (ITU) of QRIS among students in Pontianak City with Trust as an intervening variable. The research method used a quantitative approach with an associative design and data collection through a questionnaire distributed to 100 QRIS users. Data analysis was conducted using Structural Equation Modeling (SEM) with Smart-PLS. The results of the study indicate that Perceived Ease of Use and Perceived Usefulness significantly influence Trust, and Trust significantly influences Intention to Use. Additionally, Perceived Usefulness has a significant positive direct effect on Intention to Use, while Perceived Ease of Use does not have a significant direct effect on Intention to Use. The Trust variable acts as a significant mediator in the relationship between Perceived Ease of Use and Perceived Usefulness with Intention to Use. These findings indicate that perceived ease and perceived usefulness enhance students' trust in QRIS, which ultimately drives their intention to use QRIS sustainably.